How much training do road racers in USA Cycling actually do? An observational study of 543 athletes, by racing category and gender - Sroka, R. J.; Fleming, J. K.; Sims, S. L.; Coe, D. P.; Springer, C. M.; Bassett, D. R. (Journal of Science and Cycling, 2025)
Advances in bicycle instrumentation and social media applications make it possible to quantify training and racing. PURPOSE: The primary purpose was to compare training volume of USA Cycling (USAC) road racers, split out by racing category and gender. A secondary purpose was to compare power profiles of these groups. METHODS: Part 1. USAC racers with a Strava® account were selected. Using 2019 data uploaded from GPS head units, 543 racers (279 men, 264 women) were studied. Part 2. A subset of racers with power meters (N=346) were contacted to obtain demographic information and peak power data (5-s, 1-min, 5-min, 20-min, and 1-h). 92 racers (67 men, 25 women) agreed to participate. ANOVAS were used to compare annual training/racing metrics and power data across categories and genders. RESULTS: Part 1. Training/racing volumes (annual hours, distances, races, and ride days) rose significantly as the level of expertise increased. There were significant gender differences for pros (p<0.001) for all variables except ride days, but there were no gender differences within categories 2, 3, 4, and 5. Part 2. In terms of peak power (W·kg-1), there were significant main effects for category and gender (p<0.001), but no significant interactions. Overall, men produced more power than women. Categories 1/2 produced significantly more power than categories 3, 4, and 5, but the differences between categories 3, 4, and 5 were marginal. CONCLUSION: Cycling coaches can use this information to develop training programs for bicycle road racers at all levels, and for tracking their progress.